2020
DOI: 10.1186/s12915-020-00865-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of African swine fever virus-like elements in the soft tick genome provides insights into the virus’ evolution

Abstract: Background African swine fever virus (ASFV) is a most devastating pathogen affecting swine. In 2007, ASFV was introduced into Eastern Europe where it continuously circulates and recently reached Western Europe and Asia, leading to a socio-economic crisis of global proportion. In Africa, where ASFV was first described in 1921, it is transmitted between warthogs and soft ticks of the genus Ornithodoros in a so-called sylvatic cycle. However, analyses into this virus’ evolution are aggravated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 82 publications
0
51
0
Order By: Relevance
“…In addition, some DNA virus EVEs appear to contribute to immune defence by RNA interference mechanisms. In the Ornithodoros soft ticks, small-interfering RNAs (siRNA) and PIWI-interacting RNAs (piRNAs) are produced from endogenous African swine fever virus-like integrations which may confer on these vectors some protection against infection by the virus [91]. In a study of arthropod genomes [40], piRNA clusters were found to be enriched in EVEs and 18.49% of these integrations resembled parvoviruses.…”
Section: Transitions Between Viruses and Transposonsmentioning
confidence: 99%
“…In addition, some DNA virus EVEs appear to contribute to immune defence by RNA interference mechanisms. In the Ornithodoros soft ticks, small-interfering RNAs (siRNA) and PIWI-interacting RNAs (piRNAs) are produced from endogenous African swine fever virus-like integrations which may confer on these vectors some protection against infection by the virus [91]. In a study of arthropod genomes [40], piRNA clusters were found to be enriched in EVEs and 18.49% of these integrations resembled parvoviruses.…”
Section: Transitions Between Viruses and Transposonsmentioning
confidence: 99%
“…In particular, ISE6 cells and I. scapularis ticks both contain many bunyaand orthomyxo-like NIRVS sequences, suggesting that ticks are a dominant host for these virus groups [101]. Furthermore, the genomes of OME/CTVM21 and other Ornithodoros moubata cell lines, as well as some populations of O. moubata ticks, harbor African swine fever virus (ASFV)-like integrated elements that may interfere with ASFV infection [102].…”
Section: Tick Cell Lines In Arbovirus Researchmentioning
confidence: 99%
“…EVEs have been identified in genomes of both insects and ticks including sequences of viruses classified within several genera [191][192][193][194][195]. For example, the ASFV-related EVEs within the genomes of O. moubata ticks and cell lines are likely the origin of siRNA and piRNA interference responses against ASFV in ticks [102]. While infection of O. moubata and O. porcinus ticks resulted in detection of low levels of viral RNA transcripts, the cell lines OME/CTVM21, OME/CTVM22, OME/CTVM24, and OME/CTVM27 were resistant to infection with ASFV, with no detectable viral transcription.…”
Section: Tick Cell Linesmentioning
confidence: 99%
“…However, in recent years, a novel way of analyzing virus evolution, which is the analysis of endogenous viral elements (EVEs)—ancient viral sequences integrated into the host genome revealed that a large and diverse population of sequences derived from nonretroviral viruses in animal genomes were identified and maintained in the host genome over many millions of year s ( 46 ). In a previous study, it was proven that ASFV and its hosts have undergone a long time of coevolution, and endogenous viral elements of ASFV might have been integrated into transmitted vector soft tick genomes ( 47 ). However, how did the viral genes integrate into the host genome?…”
Section: Discussionmentioning
confidence: 99%